Implementasi Keamanan Jaringan Hotspot dengan Metode Address List pada RB MikroTik di SMKIT Nurul Qolbi - Ramadhan , Ilham Anwar; Purnomo , Rakhmat; Rejeki , Sri (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
SMKIT Nurul Qolbi uses the internet as a means of promotion, marketing, learning and practical communication to teachers, students, and school employees. But the SMKIT Nurul Qolbi network has not implemented hotspot network security in sharing and managing internet connections to teachers, students, and school staff computers. Without hotspot network security, many computers use the internet irregularly, causing other computers to not get a fair share of internet access. Due to the uneven internet connection, this causes disruption of school operations, so that it has an impact on the school's losses, both material and managerial. The absence of hotspot network security at SMKIT Nurul Qolbi is exacerbated by the large number of teachers, students, and school employees who do not use the internet to access needs related to work and learning. There are still many teachers, students, and school employees who use the internet to access social media sites such as Facebook, Twitter, and other sites that have nothing to do with work and learning, making the hotspot internet ineffective at Nurul Qolbi's SMKIT. Therefore, to maximize internet access found at SMKIT Nurul Qolbi, hotspot network security is needed. With hotspot network security, it is hoped that all computers can use the internet smoothly and stably even though all computer units use the internet at the same time and with hotspot network security it is hoped that it can increase the productivity of teachers, students and school employees.